Offshore renewable energy: ecological implications of generating electricity in the coastal zone. - Gill, Andrew B. (Blackwell Publishing Ltd, 2005)
Global scale environmental degradation and its links with non-renewable fossil fuels have lead to an increasing interest in generating electricity from renewable energy resources. Much of this interest centres on offshore renewable energy developments (OREDs). The large scale of proposed OREDs will add to the existing human pressures on coastal ecosystems, therefore any ecological costs and benefits must be determined.
Keywords: coastal ecology; coastal environmental impact; enhancement; habitat disturbance; resilience; stability